PENERAPAN STRATEGI INDEX CARD MATCH UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN BAHASA INDONESIA - Riris Nur Kholidah Rambe (UIN Sumatera Utara Medan, 2018)
This study aims to find out student learning outcomes by Using Index Card Match Strategy on Indonesian Subjects Event Materials Students Class V SD IT Al-Hijrah Laut Dendang. This research is a classroom action research (PTK) is a form of action research applied in the learning activities in the classroom. The population is all students in grade V SD IT Al-Hijrah Laut Dendang. Data analysis was done by variance analysis. The findings showed: 1). The result of learning of class V student of Indonesian language of event material before using Index Card Match Strategy has not proven satisfactory, with percentage of average value is 38,57%, 2) Application of Learning Strategy Index Card Match goes according to expected that is in line with research design has been designed and responded well by students of class V, 3) Implementation of Index Card Match Strategy is very appropriate to use because the results obtained increased by 63.57% in cycle I, then in cycle II the implementation of Index Card Match Strategy also increased with the value on average 77.85%.